Psychometric properties of Postpartum Partner Support Scale-Persian version - Zahra Eslahi; Zainab Alimoradi; Nasim Bahrami; Chung‐Ying Lin; Mark D. Griffiths; Amir H Pakpour (Wiley, 2021)
Abstract Aim The aim of the present study was to translate the Postpartum Partner Support Scale (PPSS) into Persian and evaluate its psychometric properties among postpartum women. Design A total of 248 women aged 18-39 years participated in this psychometric study. The PPSS was translated into Persian using a forward‐backward method. Confirmatory factor analysis (CFA) and Rasch model analysis were used to assess the psychometric properties of the PPSS. In addition, the Edinburgh Postpartum Depression Scale (EPDS) was completed simultaneously to assess the construct validity. Internal consistency of the questionnaire was assessed by calculating the Cronbach's alpha coefficient and corrected item‐total correlation. Results The unidimensionality of the PPSS was supported in both CFA and Rasch analysis. The PPSS had a significant negative association with EPDS (r = −0.39 p < .001). The scale had excellent internal consistency (Cronbach's alpha = 0.94) and the correlation between items and total score was satisfactory. Conclusion The Persian version of PPSS with 20 items is a valid and reliable scale to assess postpartum support.